Coxsackievirus A16 in a 1-Day-Old Mouse Model of Central Nervous System Infection Shows Lower Neurovirulence than Enterovirus A71 - Hooi, Y. T.; Ong, K. C.; Tan, S.H.; Perera, D.; Wong, K. T. (Elsevier Ltd., 2020)
Coxsackievirus A16 (CV-A16) and enterovirus A71 (EV-A71) are the major causes of hand, foot and mouthdisease in young children. Although less so with CV-A16, both viruses are associated with serious neurologicalsyndromes, but the differences between their central nervous system infections remain unclear. We conducted acomparative infection study using clinically-isolated CV-A16 and EV-A71 strains in a 1-day-old mouse modelto better understand the neuropathology and neurovirulence of the viruses. New serotype-specific probes for insitu hybridization were developed and validated to detect CV-A16 and EV-A71 RNA in infected tissues.Demonstration of CV-A16 virus antigens/RNA, mainly in the brainstem and spinal cord neurons, confirmedneurovirulence, but showed lower densities than in EV-A71 infected animals. A higher lethal dose50for CV-A16 suggested that CV-A16 is less neurovirulent. Focal virus antigens/RNA in the anterior horn white matterand adjacent efferent motor nerves suggested that neuroinvasion is possibly via retrograde axonal transport inperipheral motor nerves.